A 10-Year Follow-up Survey of Treatment Abandonment of Children With Acute Myeloid Leukemia in Suzhou, China. Issue 6 (August 2016) - Hong, Dan; Zhou, Chenyan; He, Hailong; Wang, Yi; Lu, Jun; Hu, Shaoyan
Abstract : A survey of the clinical data on acute myeloid leukemia (AML) over the past 10 years in the treatment center of Children's Hospital was presented. The aim of the study was to identify the factors influencing the treatment abandonment rate (AR) of AML. Of the 474 AML cases examined, 264 were abandoned (55.7%). The most important factor affecting AR appeared to be the AML subtype—that is, the M3 versus non-M3 (42% vs. 60%). Patient age was observed to be closely related to AR—the older the patients, the lower the AR—and infants had the highest prevalence of abandonment (84.2%). The patient's residential location was markedly correlated to AR, which was almost inversely proportional to the size of the township where the patient came from. From large cities, intermediate and small towns to countryside villages, the AR increased linearly. So was the correlation with health insurance coverage, which decreased in the same way. Sex and karyotypes did not affect AR. In conclusion, the patients' financial burden and the perceived incurability of AML were the 2 leading factors dominating the decision for abandonment in parents and caregivers.